Seed-Specific Overexpression of SPL12 and IPA1 Improves Seed Dormancy and Grain Size in Rice - Qin, Miaomiao; Zhang, Yan; Yang, Yanmei; Miao, Chunbo; Liu, Shenkui (Frontiers in Plant Science, 2020)
Pre-harvest sprouting (PHS) often results in reduced grain yield and quality and is a major problem in cereal production. Improved seed dormancy would inhibit PHS. Here we show that seed-specific overexpressions of two SQUAMOSA-PROMOTER BINDING PROTEIN-LIKE (SPL) genes SPL12 and IPA1 enhance seed dormancy and inhibit PHS without noticeable effects on shoot architecture in rice. In addition, seed-specific overexpression of IPA1 also increases grain size and thus improves grain productivity. Furthermore, our results suggest that SPL12 enhance the seed dormancy through directly regulating many genes in the gibberellin (GA) pathway. This research provides an efficient method to suppress PHS and will facilitate breeding elite crop varieties.